GENE-29. INCREASED COPY NUMBER BURDEN (CNB) IS ASSOCIATED WITH GRADE IN IDH-MUTANT, 1p/19q-CODELETED OLIGODENDROGLIOMAS. (11th November 2019) - Brown, Desmond; Yamada, Seiji; Kollmeyer, Thomas; Decker, Paul; Kosel, Matthew; Praska, Corinne; Raghunathan, Aditya; Giannini, Caterina; Lachance, Daniel; Eckel-Passow, Jeanette; Jenkins, Robert
Abstract: BACKGROUND: Oligodendrogliomas are classified as either WHO grade II or III depending on histologic features. Grade often influences treatment decisions. However, there is variability in patient outcome within tumors of similar grade. We hypothesized that copy number burden (CNB) and specific copy number variants (CNV) might be associated with oligodendroglioma grade and prognosis. METHODS: Copy number array analyses were performed on 285 molecular oligodendrogliomas (IDH-mutant, 1p/19q-whole arm-codeleted) from the Mayo Clinic internal and consult neuropathology practice and 167 TCGA molecular oligodendrogliomas. CNB was defined as the total number of copy number alterations. The association of CNB and CNV with grade and overall survival (when available) was assessed. All Mayo and TCGA data were evaluated using the ChAS software suite (Thermo- Fisher) and blindly reviewed by a clinical cytogeneticist (RBJ). RESULTS: The mean CNB was 5.0 and 10.4 in the Mayo WHO grade II and III oligodendrogliomas, respectively (p = 5.4 x 10 –17 ). Among the TCGA WHO grade II and III oligodendrogliomas the mean CNB was 4.4 and 5.3, respectively (p = 0.034). Common CNVs (occurring in at least 5% of cases) were -4/4q-, +8/8q+, -9/9p-/cnLOH 9p, +11/11q+, -14/14q-, -15 and -18/18q-. Of these, -9/9p-/cnLOH 9p was significantly associated with higher grade in both the Mayo and TCGA cohorts (p = 8.3 x 10 -10 and 0.018, respectively). In the TCGA cohort the presence of >10 CNVs or +11/11q+ was associated with a poorer survival (p = 0.016 and 0.006, respectively). CONCLUSIONS: CNB is significantly associated with WHO grade in IDH-mutant, 1p/19q co-deleted oligodendrogliomas. The presence of a significantly elevated CNB in some WHO grade II tumors may be suspicious for the presence of unappreciated grade III histologic features. Longer follow-up will be necessary to determine if CNB or single CNVs are associated with survival.